Raw physical oceanography and ocean current velocity data from mooring AWI229-14 in the Weddell Sea, January 2019 – March 2022 - Mario Hoppmann; Markus A Janout; Jacob Allerholt; Carina Engicht; Rainer Graupner; Pedro Llanillo; Matthias Monsees; Gerd Rohardt; Stefanie Spiesecke; Karolin Thomisch; Olaf Boebel; Mario Hoppema (PANGAEA, 2024)
Time-series data of physical oceanography and ocean current velocity were obtained from mooring AWI229-14 in the northeastern Weddell Sea between January 2019 and March 2022 as part of the Hybrid Antarctic Float Observing System (HAFOS). The mooring was deployed during RV POLARSTERN expedition PS117, and recovered during PS129. The attached archive contains raw data files of 11 Seabird SBE37 MicroCATs (nominal depths: 82m, 133m, 184m, 235m, 257m, 355m, 455m, 555m, 655m, 754m, 5015m; sampling interval 2h), and two Nortek Aquadopp current meters (nominal depths: 256m, 755m; sampling interval 1h). The mooring also included a Develogic Sonovault (nominal depth: 329m; raw data not publicly available) for passive acoustic monitoring. Auxiliary information such as sensor calibration sheets, mooring diagrams, and schedule files are also provided, if applicable. The upper four MicroCATs were attached to a rope segment on a 300kg weak link, which was still intact upon recovery. The 754m MicroCAT did not record any data. The 184m MicroCAT was programmed to an interval of 700s instead of 2h.
In: Hoppmann, Mario; Janout, Markus A: Collection of raw datasets from oceanographic moorings in the Weddell Sea, Antarctica, in 2019 - 2026 [dataset publication series]. PANGAEA, https://doi.pangaea.de/10.1594/PANGAEA.971906 (dataset in review)